Substitusi Terigu dengan Tepung Kernel Biji Mangga pada Produksi Cookies - Fajriyati Mas'ud (Journal of Sustainable Research In Management of Agroindustry (SURIMI), 2023)
Mango seed kernel flour contains high carbohydrates, besides that it also contains almost equal levels of protein and fat, so it has the potential to be used as a substitute for wheat flour in making cookies. This study examined the effects of tape yeast and tempeh yeast at concentrations of 1%, 2% and 3% and fermentation times of 15, 28 and 41 h, so there were 18 experimental units. The best results were obtained by using 2% tempeh yeast for 41 hours, namely 7.18% protein. Further optimization of the fermentation process study gave optimum results in the fermentation process of 2.23% tempeh yeast in 500 g of mango seed kernel flour for 41,04 h. Under these processing conditions, mango seed kernel flour can be produced with a protein content of 7.24%. Furthermore, for the application of fermented mango seed kernel flour as a substitute for wheat flour in making cookies, the best results were obtained at a ratio of 30% mango kernel flour and 70% wheat flour based on the taste and aroma of the cookies product. Substitution of wheat with mango kernel flour is only feasible organoleptically at a maximum level of 30%.